An analysis and selection of distribution transformer for losses reduction - Suechoey, B.; Ekburanaway, J.; Kraisnachinda, N.; Banjongjit, S.; Chompoo-Inwai, C.; Kando, M. (My University, 2000)
Thailand's medium-sized industries, with demands ranging from 30-1999 kW., currently need to select transformers that provide the highest efficiency regarding transformer losses. This is partly because the energy authorities that provide the electricity have fixed the loss ratio values for transformers. In this paper, an analysis of how to select the suitable size of transformer is presented. The considered factors include efficiency, losses, rating, capital cost throughout the transformer commission time, the cost of the energy, and % interest rate. The analysis includes an example of calculation and selection.
Keywords: Capital Cost; Cost to own; demand charge; Distribution Transformer; Interest rate; Loss Ratio; no load loss; Present -Worth factor; transformer commission time; transformer loading factor